Indução, caracterização bioquímica e histológica de calos em Cenostigma pyramidale [tul.] Gagnon & G.P. Lewis - Carvalho Filho, Rosembrando Sosthenes Leite (2022)
Cenostigma pyramidale [Tul.] Gagnon & G.P. Lewis, is a tree belonging to the Fabaceae family, which has medicinal and timber uses. This work aimed to study the callogenesis of catingueira, as well as to analyze biochemically and histologically the callus obtained in order to identify embryogenic potential. Callus induction occurred in two different ways. In the first, leaf explants were inoculated in MS culture medium supplemented with different concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D) combined with concentrations of 6-benzylaminopurine (BAP) and glutamine. After 45 days of culture, the following were evaluated: percentage of explants that formed callus, fresh mass of explants with callus, percentage of explant area covered by callus, coloration and texture. In the second, leaf explants were subjected to auxin pulse treatment in liquid MS medium containing or not 210 μM of 2,4-D in the absence and presence of 7.0 μM of 2,4-D, 5.0 μM of BAP, and 0.68 mM of glutamine. For the growth curve, the fresh mass of explants with and without callus up to day 77 of culture was weighed at 7-day intervals, totaling 12 periods. In each period, samples were collected for histomorphological analysis and determination of the content of reducing sugars (RA), sucrose and total soluble sugars (TSA). Callus induction was observed in C. pyramidale using foliol segments, both in auxin pulse and in continuous use of BAP, 2,4-D and glutamine in culture medium. The histomorphological analyses revealed the presence of cells with characteristics similar to those with meristematic potential in the callogenesis experiment with BAP, 2,4-D and glutamine, while the auxin stress experiment was not efficient to do so. The growth curve showed sigmoidal behavior with five distinct phases: lag, exponential, linear, deceleration, and decline. The RA content was decreasing and was detected until day 21 of the growth curve. The content of TSA and sucrose showed a peak at the end of the lag phase and degradation in the exponential phase with stability and slight reduction until the decline phase.